Determinan Kejadian Kanker Payudara Pada Wanita Di Rsud Arifin Achmad Provinsi Riau Tahun 2019 - Aulia Astri; Syamsul Bahri Rivaí; Sri Desfita; Jasrida Yunita; Nurlisis (Sistem Informasi, 2020)
Breast cancer is among the most discussed cancers because of its malignancy which often ends in death. Based on the 2013 Basic Health Research Data (Riskesdas), the number of breast cancer patients reached 61,682 cases in Indonesia. As in Riau Province according to the medical records of Arifin Achmad Regional Hospital, breast cancer ranks first with 325 cases out of 580 cases in Irna Surgical Cendrawasih in 2016. Purpose of this study was to determine the determinants of breast cancer incidence in women in Arifin Achmad Regional Hospital in Riau Province in 2019. This research uses a quantitative research design with a case control approach. The research instrument used was a questionnaire. The sampling technique was Consecutive Sampling. This research was conducted in May to July 2019. Case samples in this study were women who were diagnosed positive for breast cancer and control samples were women who were diagnosed with negative breast cancer. Univariate and bivariate data analysis with chi square test and multivariate analysis using Simple Logistic Regression test. The results showed the most dominant variables related to cause and effect with the incidence of breast cancer were a history of abortion 3.7 times, a history of hormonal contraceptive use 5.4 times, the age of first child birth> 35 years 3 times, and the number of nulliparous children 2.3 times. It is expected that health workers and related institutions will be able to provide health education regarding the positive and negative impacts of contraceptive use, the importance of planning the marriage age and promoting family planning programs that have been launched by the government.